OʻQUVChILARDA EKOLOGIK ONG VA MAS’ULIYATNI ShAKLLANTIRISh USULLARI - Toʻxtayeva, Z.Sh.; Rayimova, N.B. (SCIENCE and SOCIETY, 2025)
This article highlights the problem of the development of environmental awareness and culture among students. The importance of providing environmental knowledge and skills to students and youth in order to protect the environment, understand environmental issues and achieve sustainable development was emphasized. The role of environmental education, effective methods and pedagogical approaches in the educational process is also analyzed.
Keywords: ecological culture; ecological consciousness; environment; ecological education; youth; education